2012
DOI: 10.1016/j.mambio.2011.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the border? Structure of the red deer (Cervus elaphus) population from the Bavarian–Bohemian forest ecosystem

Abstract: a b s t r a c tAnthropogenic impact such as overhunting and habitat fragmentation has reduced the total red deer population (Cervus elaphus) across Europe. In Germany remaining subpopulations are even confined to designated areas with limited or no gene flow among them. Red deer populations inhabiting the Bavarian-Bohemian forest ecosystem had been divided by a fortified State border between Germany and former Czechoslovakia. To assess red deer genetic diversity more than two decades after the removal of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…Out of the ten haplotypes found in the ancient Norwegian dataset five are shared with other countries. Of these, the two central haplotypes NO1 and NO4 are widespread, being present in Scotland and the border forests between Germany and the Czech Republic [14,23,25], with NO4 also found in Spain [14], and NO1 being one of the most common types found in the Scottish highlands today [25]. None of the extant Norwegian haplotypes are shared with other Scandinavian countries; although the ancient NO6 is found in Denmark today [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the ten haplotypes found in the ancient Norwegian dataset five are shared with other countries. Of these, the two central haplotypes NO1 and NO4 are widespread, being present in Scotland and the border forests between Germany and the Czech Republic [14,23,25], with NO4 also found in Spain [14], and NO1 being one of the most common types found in the Scottish highlands today [25]. None of the extant Norwegian haplotypes are shared with other Scandinavian countries; although the ancient NO6 is found in Denmark today [27].…”
Section: Discussionmentioning
confidence: 99%
“…The age of the samples range from the Mesolithic to the Late Middle Ages (c. 7,000-500 yr BP) and all samples were collected from the University Museum of Bergen. Data on contemporary Norwegian and European mtDNA diversity were compiled from the literature ( [14,23-29], Haanes et al . unpublished results), excluding sequences from populations described by authors as translocated by humans during the last centuries.…”
Section: Methodsmentioning
confidence: 99%
“…The mountain white-eye (Zosterops poliogaster) inhabits both of these habitats, and genetic data from this species reflect the divergent habitat histories of these now similar habitat structures. Fickel et al (2012) found that only 20 years (or roughly three generations) after the fall of the Iron Curtain, panmixia was re-established in red deer (Cervus elaphus) from the Bavarian-Bohemian forest ecosystem. By contrast, the Taita Hills population sampled at different time points over the past 20 years shows a strong increase in genetic differentiation among local subpopulations (Habel et al, in press).…”
Section: The Relevance Of Habitat Histories -Habitat Persistence Vmentioning
confidence: 99%
“…Pérez‐González et al () reported genetic structure in free‐ranging red deer in Spain based on fragmented habitats. Fickel et al () looked at genetic structure of red deer populations 20 years after a border was removed from Germany and the former Czechoslovakia. They collected genetic data after populations were once again connected.…”
Section: Discussionmentioning
confidence: 99%